Increased number of monocytes and plasma levels of MCP‐1 and YKL‐40 in first‐episode psychosis. (21st August 2018) - Orhan, F.; Schwieler, L.; Fatouros‐Bergman, H.; Malmqvist, A.; Cervenka, S.; Collste, K.; Flyckt, L.; Farde, L.; Sellgren, C. M.; Piehl, F.; ,; Engberg, G.; et al.
Abstract : Objective: Accumulating evidence implicates immune activation in the development of schizophrenia. Here, monocyte numbers, monocyte chemoattractant protein‐1 (MCP‐1) and chitinase‐3‐like protein 1 (YKL‐40) were investigated in plasma and cerebrospinal fluid (CSF) in first‐episode psychosis (FEP) patients. Method: CSF and blood were sampled from 42 first‐episode psychosis (FEP) patients and 22 healthy controls. The levels of YKL‐40 and MCP‐1 were measured using electrochemiluminescence assay, and blood monocytes were counted using an XN‐9000‐hematology analyzer. Results: We found higher plasma levels of MCP‐1 and YKL‐40 in FEP patients compared with healthy controls, a condition that was unrelated to antipsychotic and/or anxiolytic medication. This was combined with an increased number of blood monocytes and a borderline significant increase in YKL‐40 levels in the CSF of tobacco‐free FEP patients. Plasma or CSF chemokines or blood monocytes did not correlate with the severity of symptoms or the level of functioning. Conclusion: These data demonstrate activation of monocytes in FEP and strengthens the idea of an immune dysfunction of psychotic disorders. Further studies are required to perceive a role of YKL‐40 and MCP‐1 in the initiation and progression of schizophrenia.